Effect analysis of fuse deposition modeling processes on mechanical properties of wood plastic composites - Arias-Nava, Elias H. (2018)
Nowadays, fuse deposition modeling is a growing fabrication technology for developing new products. When using plastics, these processes present various challenges related to fusion distribution, fuse deposition paths, part orientation, and layer thickness among others. The problem is increased however, when fabricating parts using materials that are limited in the literature. The use of different equipment may produce variations in the mechanical properties of a product. This study analyzes the effects of process parameters as well as the use of two different fuse deposition models on mechanical properties of wood-plastic composites. A design of experiments is proposed as a methodology to evaluate the objectives of the study. Results show that makerbot™ is a promising option to improve ultimate tensile strength exposed to different conditions of fabrication. It was observed that the makerbot™ and the printrbot™ had a significant difference in the tensile strength in the wood-plastic composite filled samples. The layer thickness of the samples has a significant impact in the mechanical properties, the tensile strength decreases as the thickness increases